LAPORAN KASUS: KEMBAR SIAM TIPE HETEROPAGUS (PARASIT) - Fahruddin, Ahmad; Suhaimi, Donel (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2024)
Conjoined twins are a rare form of multiple pregnancy that occurs due to incomplete division of the zygote. In this report, there was a case of heteropagus conjoined twins where the parasite attached to the oropharyngeal autosite area. Considering the fact that multiple pregnancies with parasitic fetuses are very rare, we consider this case report important and useful. This case report aimed to determine the management of heteropagus conjoined twins. The subject of the case study in this case study was a pregnant woman with a heteropagus conjoined twin pregnancy at Arifin Achmad Hospital in 2022. The research method used  the case study method, which is a study that explores a problem in detail, takes in-depth data and includes various sources of information. which will help doctors gain insight into the mystery of parasitic twins. In this case, the patient underwent a planned CS at 35-36 weeks of gestation, according to the findings on physical examination of the patient's baby there was a mass attached to the intraoral area, the mass showed rudimentary, acephalic and acardiac hand and foot shaped tissue. The limbs in parasites do not move and do not feel. There is no skeletal muscle in the legs and this is thought to be due to failure of myoblast differentiation caused by lack of proper innervation. The baby's condition had deteriorated because the baby's airway was disrupted due to a lump entering the stomach. Currently, the baby's condition is improving after surgery to separate the conjoined twins. Next, focus again on recovering the baby's condition.